2018
DOI: 10.3389/fphys.2018.01472
|View full text |Cite
|
Sign up to set email alerts
|

Shining New Light on the Structural Determinants of Cardiac Couplon Function: Insights From Ten Years of Nanoscale Microscopy

Abstract: Remodelling of the membranes and protein clustering patterns during the pathogenesis of cardiomyopathies has renewed the interest in spatial visualisation of these structures in cardiomyocytes. Coincidental emergence of single molecule (super-resolution) imaging and tomographic electron microscopy tools in the last decade have led to a number of new observations on the structural features of the couplons, the primary sites of excitation-contraction coupling in the heart. In particular, super-resolution and tom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(28 citation statements)
references
References 106 publications
0
28
0
Order By: Relevance
“…On the other hand, the purely chemical approach of EExM is likely more accessible to cell biologists who often have limited expertise in instrumentation development and the intricacies of fluorophore photochemistry, as argued previously. 62…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the purely chemical approach of EExM is likely more accessible to cell biologists who often have limited expertise in instrumentation development and the intricacies of fluorophore photochemistry, as argued previously. 62…”
Section: Discussionmentioning
confidence: 99%
“…The variability in TT-jSR membrane distance observed here does not preclude accommodation of RyR, whose cytoplasmic component is thought to extend around 12 nm beyond the SR membrane. Recent molecular imaging results have shown that the in-plane arrangement of RyR is highly non-uniform, with small and larger clusters of RyR whose topology is susceptible to changes in cellular environment [ [46] , [47] , [48] , [49] , [50] , [51] ]. Our observations are consistent with such a dynamic arrangement, and in regions of the dyad lacking RyR, the two membranes may either be pulled closer together (aided, potentially, by junctophilin), or be less well linked and more separated.…”
Section: Discussionmentioning
confidence: 99%
“…The calcium transient data suggest improved coupling of RyRs with LTCC to form functional dyads in T3 treated myocytes, even though the total protein content was largely unchanged. Recent advancements in microscopic nanoimaging using STORM technology that allows visualization of single molecules or clusters of RyR and LTCC proteins at the junctional SR-TT microdomains will advance our understanding of the effects of T3 on the formation of the RyR-LTCC dyads in failing cardiomyocytes (Jayasinghe et al 2018; Shen et al 2019).…”
Section: Discussionmentioning
confidence: 99%